2021
DOI: 10.1158/1078-0432.ccr-20-3310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Prostate Cancer Targeting CD46 Using ImmunoPET

Abstract: Purpose: We recently identified CD46 as a novel therapeutic target in prostate cancer. In this study, we developed a CD46-targeted PET radiopharmaceutical, [89Zr]DFO-YS5, and evaluated its performance for immunoPET imaging in murine prostate cancer models. Experimental Design: [89Zr]DFO-YS5 was prepared and its in vitro binding affinity for CD46 was measured. ImmunoPET imaging was conducted in male athymic nu/nu mice bearing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 40 publications
12
43
0
Order By: Relevance
“…The radiolabeling of 89 Zr oxalate to NPs was accomplished in a single-step chelation with the deferoxamine B ligand (DFB) present on the surface of the NPs (Figure a). ,, To optimize the appropriate DFB ligand concentration, NPs with different wt % of PLGA- b -PEG-DFB conjugates were subjected to 89 Zr radiolabeling using previously described conditions. ,, The reaction yield was determined at 1 h by iTLC and also by measuring the isolated radioactivity following purification using centrifugation. These yields are summarized in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radiolabeling of 89 Zr oxalate to NPs was accomplished in a single-step chelation with the deferoxamine B ligand (DFB) present on the surface of the NPs (Figure a). ,, To optimize the appropriate DFB ligand concentration, NPs with different wt % of PLGA- b -PEG-DFB conjugates were subjected to 89 Zr radiolabeling using previously described conditions. ,, The reaction yield was determined at 1 h by iTLC and also by measuring the isolated radioactivity following purification using centrifugation. These yields are summarized in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Representative iTLC spectra of DFB(25) NP reaction mixture before and after purification are presented in Figures 3c,d The relative binding affinities of the formulated NPs were estimated, similar to our prior report, by 68 Ga-PSMA-11-based competitive radioligand binding assay (Figure 4c). 27,44 Although the IC 50 values of these NPs were observed in the μg/mL range, a relatively lower IC 50 value was obtained for DFB( 25)ACUPA(75) NPs (0.11 μg/mL) than that of DFB( 25)ACUPA( 25) NPs (0.59 μg/mL). This demonstrated the superior binding affinity of DFB( 25)ACUPA(75) NPs, owing to the higher number of ACUPA ligands on the surface of the NPs.…”
Section: Radiolabeling Of Nanoparticlesmentioning
confidence: 90%
See 1 more Smart Citation
“…The ADC is in a multi-center phase I trial (NCT03575819) and a phase I/II combination trial (NCT05011188) for mCRPC. Our recent work also demonstrated that the 89 Zr radiolabeled YS5 ( 89 Zr-DFO-YS5) can detect prostate cancer in vivo in both PSMA positive and PSMA negative mCRPC cell line xenograft (CDX) models and patient derived xenograft (PDX) models of both the adenocarcinoma and neuroendocrine subtypes (17), and a first-in-human study of this novel PET agent is ongoing in mCRPC patients (NCT05245006). In this study, we report the synthesis and evaluation of tolerability and therapeutic efficacy of the 212 Pb-radiolabeled human antibody YS5 ( 212 Pb-TCMC-YS5) in multiple prostate cancer small animal models, including subcutaneous CDX, intraprostate orthotopic CDX, and prostate cancer PDX models.…”
Section: Introductionmentioning
confidence: 99%
“…CD46 is a membrane protein that protects cells from complement attack. 27 A high expression of CD46 has been observed in several cancers including prostate cancer, 28 with clinical and experimental data supporting an association between increased CD46 expression and malignant transformation, and metastasizing potential. [29][30][31] CD46 is also being investigated as a target in early-phase clinical trials for a variety of cancers including advanced prostate cancer (e.g.…”
mentioning
confidence: 94%